Cutis laxa with pulmonary emphysema, conjunctivochalasis, nasolacrimal duct obstruction, abnormal hair, and a novel FBLN5 mutation - Kantaputra,P.N.I. (Wiley-Liss Inc., 2015)
We report on a 4-year-old girl with autosomal recessive cutis laxa, type IA, or pulmonary emphysema type (ARCL1A; OMIM #219100), with loose and wrinkled skin, mitral and tricuspid valve prolapse, conjunctivochalasis, obstructed nasolacrimal ducts, hypoplastic maxilla, and early childhood-onset pulmonary emphysema. Mutation analysis of FBLN5 showed a homozygous c.432C>G missense mutation, and heterozygosity in the parents. This is predicted to cause amino acid substitution p.Cys144Trp. Conjunctivochalasis or redundant folds of conjunctiva and obstructed nasolacrimal ducts have not been reported to be associated with FBLN5 mutations. Histopathological study of the conjunctival biopsy showed that most blood vessels had normal elastic fibers. The gingiva appeared normal, but histologically elastic fibers were defective. Scanning electron micrography of scalp hair demonstrated hypoplastic hair follicles. The cuticles appear intact underneath the filamentous meshwork. © 2014 Wiley Periodicals, Inc.